Concrete Mixtures with High Microfines (2006)
Two projects were performed to evaluate the effect of the amount and type of microfines (material passing the No. 200 sieve), as well as the effect of shape, texture, and grading of aggregates on concrete behavior. In the first project, several manufactured fine aggregates (MFA) and one natural sand were used for mortar and concrete mixtures, without chemical admixtures. Generally, concrete with MFA was stiffer and less workable than concrete with natural sand, but in most cases MFA resulted in higher compressive and flexural strengths, higher resistance to chloride penetration, and higher abrasion resistance. In the second project, five aggregates with varied shape and texture were used to make concrete with microfines, chemical admixtures, and supplementary cementing materials. Significant variations due to the combined effect of shape and texture of aggregate, grading, and the type and amount of microfines were found. It was also found that chemical admixtures and cementing materials can be used to enhance workability of concrete with high microfines.